„Ćwiczę widzenie”. O twórczości Jadwigi Stańczakowej - Ładoń, Monika (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
Jadwiga Stańczakowa was a blind writer, who was more known as a friend of Miron Białoszewski than for her own literary work. Meanwhile, she is the author of several books of poetry, autobiographical prose and a diary. Miron Białoszewski was certainly master for her, thanks to him she began to write about his own blindness. Although that all her work was connected with Białoszewski, it is worth to hear her own voice, especially in the context of disability studies. In this article the author is trying to bring out the poetess of the Białoszewski’s shadows. First of all, the author pointed out that blindness was a magical experience treated as a basis of lirycs. But the dysfunction of sight has also been a cause of recurring depressions. The writing during this ‘double disease’ was particularly difficult and made sense of self-therapy.